Groundnut production in the watershed areas of north-eastern hills region of India - Das, Anup; Patel, D; Layek, Jayanta; Babu, Subhash; GI, Ramkrushna (Indian Farming, 2018)
Field experiments and demonstrations conducted across the north-eastern hills region revealed that groundnut is a potential crop for the region. The crop under optimum management condition gives at least 2.5 to 3 tonne/ha pod yield. Recommended NPK + lime application in furrow (500 kg/ha) was found suitable for optimum groundnut yield. For organic groundnut production application of farmyard manure 10 tonne/ha along with liming and application of biofertilizer is recommended. Groundnut varieties like ICGS 76, BAU 13, GSMG 84-1 could produce a pod yield of 2.8 to 3.0 tonnes/ha under mid hill conditions of northeastern region. Maize+ groundnut (2:2) and groundnut-rapeseed were found profitable for enhancing system productivity and conserving soil health. On an average, a net income of Rupees 45,000 may be obtained from a well-managed groundnut crop. With adequate support for processing, value addition and marketing, groundnut can be a potential crop for livelihood improvement of hill farmers. Groundnut has the potential to conserve natural resources, improve soil-health and enhance system productivity and livelihood of farmers in north-eastern region.